1997
DOI: 10.1073/pnas.94.5.2079
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, transient, and highly localized induction of plastidial ω-3 fatty acid desaturase mRNA at fungal infection sites in  Petroselinum crispum

Abstract: Parsley (Petroselinum crispum) plants and suspension-cultured cells have been used extensively for studies of non-host-resistance mechanisms in plant͞pathogen interactions. We now show that treatment of cultured parsley cells with a defined peptide elicitor of fungal origin causes rapid and large changes in the levels of various unsaturated fatty acids. While linoleic acid decreased and linolenic acid increased steadily for several hours, comparatively sharp increases in oleic acid followed a biphasic time cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 62 publications
3
40
1
Order By: Relevance
“…In Petroselinum crispum, the fungal elicitor peptide Pep25 has been shown to stimulate rapid 18:3 9c,12c,15c (α-linolenate, 2P) production and, concomitantly, decrease 18:2 levels over a 2-hour period in cultured cells, protoplasts, and plant leaves [101]. α-Linolenate is a necessary lipid for the biosynthesis of the octadecanoid jasmonate in plants, a signaling component involved in defensive response and development, while polyunsaturated fatty acids generally provide an oxidative sink to consume reactive oxygen species [102].…”
Section: Cloning and Expression Of The Lipid-desaturating Components Ofmentioning
confidence: 99%
“…In Petroselinum crispum, the fungal elicitor peptide Pep25 has been shown to stimulate rapid 18:3 9c,12c,15c (α-linolenate, 2P) production and, concomitantly, decrease 18:2 levels over a 2-hour period in cultured cells, protoplasts, and plant leaves [101]. α-Linolenate is a necessary lipid for the biosynthesis of the octadecanoid jasmonate in plants, a signaling component involved in defensive response and development, while polyunsaturated fatty acids generally provide an oxidative sink to consume reactive oxygen species [102].…”
Section: Cloning and Expression Of The Lipid-desaturating Components Ofmentioning
confidence: 99%
“…5). Also potentially related to oxylipin signaling, a sorghum gene (BI245631) with homology to a JA-regulatory protein from Arabidopsis was strongly upregulated by both SA and MeJA at the 27-h time point, while MeJA specifically, strongly, and rapidly induced transcription of an apparent w-3 fatty acid desaturase homolog (BG048471; Table I, Fatty acid metabolism/ JA synthesis), a lipid modification enzyme previously implicated in response to fungal elicitation (Kirsch et al, 1997).…”
Section: Genes Involved In Lipid Metabolism and The Oxylipin Pathway/mentioning
confidence: 99%
“…Cells were harvested by centrifugation and the pellet was lyophilized and subsequently treated with 1 mL of methanolic HCI. Preparation of the fatty acid methyl esters and GC analysis were performed as described by Kirsch et al (1997). The fatty acid methyl esters were identified by comparison of their retention times with those of authentic standards.…”
Section: Crowth and Fatty Acid Analysis Of Transformed Yeast Cellsmentioning
confidence: 99%
“…Using a cDNA encoding a plastid-localized w-3 FAD and two partial cDNAs representing FAD-like genes, we recently demonstrated that the corresponding mRNAs were strongly induced in parsley cells upon treatment with the Pep25 elicitor (Kirsch et al, 1997). A closely related partial cDNA, previously isolated and designated ELI12 (Somssich et al, 1989), was found to share considerable sequence similarity with microsomal w-6 FADs and has been used as a probe to isolate a gene (FAD2 locus) encoding a microsomal 0-6 FAD gene from Arabidopsis thaliana (Kirsch et al, 1997).…”
Section: Cloning Of a Putative A12 Fad C D N Amentioning
confidence: 99%
See 1 more Smart Citation